Novel Therapeutic Targets in Liver Fibrosis - Zhang, Jinhang; Liu, Qinhui; He, Jinhan; Li, Yanping (Frontiers in Molecular Biosciences, 2021)
Liver fibrosis is end-stage liver disease that can be rescued. If irritation continues due to viral infection, schistosomiasis and alcoholism, liver fibrosis can progress to liver cirrhosis and even cancer. The US Food and Drug Administration has not approved any drugs that act directly against liver fibrosis. The only treatments currently available are drugs that eliminate pathogenic factors, which show poor efficacy; and liver transplantation, which is expensive. This highlights the importance of clarifying the mechanism of liver fibrosis and searching for new treatments against it. This review summarizes how parenchymal, nonparenchymal cells, inflammatory cells and various processes (liver fibrosis, hepatic stellate cell activation, cell death and proliferation, deposition of extracellular matrix, cell metabolism, inflammation and epigenetics) contribute to liver fibrosis. We highlight discoveries of novel therapeutic targets, which may provide new insights into potential treatments for liver fibrosis.